A critical approach to sensorimotor contingency theory: brain as agent and conscious mind as a guide of action - Coelho, Jonas Gonçalves (Sofia, 2019)
I present and consider critically O'Regan and Noë's sensorimotor contingency theory, proposed as an alternative to solve the explanatory gap problem. I start with the criticism that these authors address the current conception of representation, according to which conscious experiences are representations of the external world produced by the brain. Afterward, I summarize the way the sensorimotor contingency theory addresses the problem of the explanatory gap, explaining the existence, form, and content of visual consciousness in terms of an "exploratory activity" mediated by sensorimotor contingency laws. Finally, in agreement with criticisms addressed to O'Regan and Noë's solution, I propose a way to face the problem of the explanatory gap, which, recognizing the relevance of the body and the external environment to the existence, form and content of visual consciousness, but privileging the role of the brain as an organ of visual consciousness, and as an agent who uses visual consciousness as a guide to initiate and maintain embodied and situated adaptive actions in the world.